(untitled) (Fiep Bulletin - online, 2013)
This study aims to contribute in a theoretical-methodological way for the discussions about game, toy and entertainment during the learning process in the Physical Education classes at school. For so much, we will bring to discussion the theoretical-methodological contributions regarding this knowledge, as well as an experience accomplished at UFPE Application School that enabled us reveal some enriched elements for teachers’ Physical Education pedagogical practice in a ludicrous perspective.